The seven valleys and The four valleys - Bahá'u'lláh (Bahá'í Publishing Trust, 1978)
Contents: The valley of search; The valley of love; The valley of knowledge; The valley of contentment; The valley of wonderment; The valley of true poverty and absolute nothingghess...